Champions for change : reducing HIV/AIDS stigma and discrimination in the Caribbean - Hackett, Volderine (CCS GeorgetownGY, 2005)
Includes conference papers which present both the challenges and prospects of the Pan Caribbean Partnership Against HIV/AIDS (PANCAP). Sets the role, road blocks and obligations of 'Champions for change', not only in the overall fight aginst HIV/AIDS but more specifically in the struggle to overcome stigma and discrimination.